Study of Charged Nanodroplet Deposition into Microcavity Through Many-Body Dissipative Particle Dynamics - Yiwei Jin; Jiankui Chen; Wei Chen; Zhouping Yin (Micromachines)
For a near-eye display, a resolution of over 10,000 pixels per inch (PPI) for the display device is needed to eliminate the “screen door effect” and have better display quality. Electrohydrodynamic (EHD) printing techniques, which have the advantages of a high resolution, wide material applicability and flexibility in patterning, have been widely used in the printing of high-resolution structures. However, due to factors such as the extremely small size of the droplets, the electric charge, the electric field, and the unavoidable positioning error, various deposition defects can occur. For droplets at a nanoscale, the dynamic deposition process is hard to observe. The continuum hypothesis fails and the fluid cannot be described by the traditional Navier–Stokes equation. In this work, the behaviors of charged nanodroplet deposition into a microcavity in an electric field are studied. The many-body dissipative particle dynamics (MDPD) method is used to examine the deformation of the nanodroplet during the impact process at a mesoscale. The dynamic process of charged droplet deposition into a microcavity under an electric field is revealed. Strategies for failure-free printing are proposed by analyzing the influences of the impact speeds, positioning errors, charge levels and electric intensities on the out-of-pixel spread length. The relationship between the internal charge moves and the deformation of the charged droplet in the deposition process is first discussed. The spreading theory of charged droplet deposition into a microcavity with a positioning error is established by analyzing the Coulombic capillary number. Moreover, the printing parameter space that results in successful printing is acquired.